Implementasi Sistem Informasi Berbasis QR Code Guna Mencegah Kerumunan dalam Antrian Wisuda - Dani Anggoro; Dolly Virgian Shaka Yudha Sakti; Sejati Waluyo (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Graduation is an inauguration event for students who have completed their studies at university. This event was attended by many people in the room. The Covid-19 pandemic requires us to adapt to being new normal, as well as graduation events. Events cannot be held as usual because everyone must follow health protocols, such as maintaining distance between people and not gathering indoors. Online graduation can be a solution, but in-person graduation is more expected by students and parents. The purpose of this study is to implement a QR Code-based information system to prevent indoor crowds and manage graduation queues. The method used in building the system is a prototype model with stages, namely analysing data, designing the system using UML diagrams, coding using the PHP Native programming language and testing using Black Box Testing. The result of this research is a web-based application that can read QR Code from students. The test results show that the application created can be a solution in holding graduation directly during the adaptation period of new habits during the Covid-19 pandemic.